Two new species of Hechtia (Bromeliaceae, Hechtioideae) from Oaxaca, Mexico - Hernández-Cárdenas, Rodrigo Alejandro; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo (Phytotaxa, 2019)
Hechtia gypsophila and H. minuta, two new species from Oaxaca, Mexico are described and illustrated. The proposed species are compared with H. pumila, taxon that present some similarities and also with other species that grow near the type localities of the two new taxa proposed. Images and a distribution map of all taxa are included.